Minat Generasi Muda dalam Usaha Tani Padi Organik di Desa Gentungan Kecamatan Mojogedang Kabupaten Karanganyar - Alfika Aninda Wahyuni; Suwarto Suwarto; Eksa Rusdiyana (Universitas Sebelas Maret, 2024)
The development of organic rice farming in Gentungan Village faced aging farmers. This research aims to assess the interest of the younger generation in organic rice farming in Gentungan Village, analyze the efforts made to increase youth interest in organic rice farming, and the impact of the existence of the Taruna Tani Lestari group. This research method uses descriptive qualitative. The location selection was purposively in Gentungan Village, Mojogedang Sub-district, Karanganyar. The number of informants in this research was 18, consisting of youth members of the Taruna Tani group, youth farmers not members of the Taruna Tani groups, and non-youth farmers—data analysis using Miles and Huberman using the Promethee method. Data validity used triangulation of sources and data collection methods. The results showed that youth interest in organic rice farming began to increase due to various efforts made by the village in collaboration with universities and other agricultural start-ups. The existing efforts include forming the Taruna Tani group, introducing technology and development of agricultural infrastructure, education and training in agriculture, collaborating with various stakeholders, establishing agro-tourism, and developing other commodities. However, the Gentungan Village government needs to formulate multiple policies in the Village Medium Term Development Plan (RPJM) related to efforts to increase youth interest in organic farming businesses to realize Gentungan Village as an Organic Village in 2030.